Assessing the Predictive Power of Frailty and Life-Space Mobility on Patient-Reported Outcomes of Disability in Older Adults with Low Back Pain - Thonprasertvat B. (2023)
Background: Frailty and decreased life-space mobility are known as risk factors to develop physical limitations leading to disability in older adults with low back pain (LBP). This cross sectional study aimed to investigate the prevalence and predictive power of frailty and life-space mobility on patient-reported outcomes of disability in older adults with LBP. Methods: The sample comprised 165 older adults with LBP who visited two tertiary care hospitals between December 2021 and February 2022. The participants responded to structured standard questionnaires. Data were analyzed using descriptive statistics and robust logistic regression. Results: More than two-thirds of participants were classified as non-frail (26.67%) or pre-frail (66.67%). Mobility restrictions and minimal to severe disability were identified. Controlling other variables, frailty (OR = 1.74, 95% CI: 1.14–2.64) and restricted life-space mobility (OR = 0.42, 95% CI: 0.26–0.67) were significantly associated with disability. Integrating frailty with life-space mobility evaluations demonstrated the highest predictive power for disability-related LBP (AUC = 0.89, 95% CI: 0.84–0.93). Conclusion: Frailty and restricted life-space mobility significantly predicted disability in older adults with LBP. Healthcare professionals should recognize the critical importance of integrating patient-reported outcomes with screening for frailty and life-space mobility limitation to optimize care or tract symptom progression.